Comparative study of various oxytocics in management of third stage of labour - Gadappa, Shrinivas N.; Sharma, Deepika; Gavit, Yogita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Causes of maternal mortality are haemorrhages, infections, unsafe abortions, and obstructed labour. 25% of these are caused by haemorrhages and are preventable, one of the measures is active management of third stage of labour (AMTSL). For prevention, treatment of postpartum haemorrhage oxytocics are available oxytocin, methylergometrine, misoprostol, prostaglandin F2α. Methods: Study was conducted, 160 patients were randomly given one of following oxytocics a) tablet misoprostol 600 µg per rectal b) Inj. Oxytocin 10 IU IM c) Inj. Methylergometrine 0.2 mg IM d) Inj. PGF2α. Duration for the delivery of placenta and amount of blood loss was measured, side effects were noted, and comparison of haemoglobin and blood loss done. Results: No significant difference in mean blood loss in all group with respect to parity and type of labour. In present study it seems that no oxytocic is superior to other in reducing the blood loss. Misoprostol has variable onset of action. Mean duration of 3rd stage in various groups is same. In respect to side effects HTN is common with methylergometrine, shivering and fever with misoprostol and diarrhoea with PGF2α. Conclusions: Study concluded that all uterotonics have some advantages, oxytocin is ultimate drug of choice in skilled hand due to its definite onset of action while Tab misoprostol in unskilled hands, other oxytocin are reserved for complementary usage and treatment of PPH but Misoprostol has variable onset of action.